Identification and Characterization of Shaker K+ Channel Gene Family in Foxtail Millet (Setaria italica) and Their Role in Stress Response - Zhang, Ben; Guo, Yue; Wang, Hui; Wang, Xiaoxia; Lv, Mengtao; Yang, Pu; Zhang, Lizhen (Frontiers in Plant Science, 2022)
Potassium (K+) is one of the indispensable elements in plant growth and development. The Shaker K+ channel protein family is involved in plant K+ uptake and distribution. Foxtail millet (Setaria italica), as an important crop, has strong tolerance and adaptability to abiotic stresses. However, no systematic study focused on the Shaker K+ channel family in foxtail millet. Here, ten Shaker K+ channel genes in foxtail millet were identified and divided into five groups through phylogenetic analysis. Gene structures, chromosome locations, cis-acting regulatory elements in promoter, and post-translation modification sites of Shaker K+ channels were analyzed. In silico analysis of transcript level showed that the expression of Shaker K+ channel genes was tissue or developmental stage specific. The transcription levels of Shaker K+ channel genes in foxtail millet under different abiotic stresses (cold, heat, NaCl, and PEG) and phytohormones (6-BA, BR, MJ, IAA, NAA, GA3, SA, and ABA) treatments at 0, 12 and 24 h were detected by qRT-PCR. The results showed that SiAKT1, SiKAT3, SiGORK, and SiSKOR were more worth for further research due to their significant changes after most treatments. The yeast complementation assay verified the inward K+ transport activities of detectable Shaker K+ channels. Finally, we found interactions between SiKAT2 and SiSNARE proteins. Compared to research in Arabidopsis, our results showed a difference in SYP121 related Shaker K+ channel regulation mechanism in foxtail millet. Our results indicated that Shaker K+ channels play important roles in foxtail millet and provided theoretical support for further exploring the K+ absorption mechanism of foxtail millet under abiotic stress.